Fournier’s Gangrene: A 4-Year Retrospective Study in a Tertiary Academic Hospital - Almas Nur Prawoto; Iswinarno Doso Saputro; Lynda Hariani; Andreas Arkhipus Dewantara (The Annals of African Surgery)
Background: Fournier’s gangrene (FG) is a necrotizing fasciitis disease that affects the genital, perianal, and perineal regions. This study investigated the demography and treatment methods of patients with FG in a 4-year period in our hospital. Methods: Medical records of 14 patients with Fournier’s gangrene who underwent treatment were analyzed retrospectively. Data on the patients were collected such as gender, age, length of stay (LOS), comorbidities, wound treatment, bacteriological cultures, and reconstructive procedures. Results: There was no significant correlation between age (p = 0.776), comorbid disease (p = 0.954), LOS or age (p = 0.221), comorbid disease (p = 0.928), and patient outcome. Wound treatment using negative pressure wound therapy (NPWT) was performed in 14% of the patients. Wound treatment had a statistically significant effect toward LOS (p = 0.044). Flaps were the most common reconstructive procedure (71.4%) followed by skin grafts (14%). Age and comorbid disease did not have an effect toward hospital LOS or patient outcome. The use of NPWT is likely related to the increased complexity of the lesion. Flaps provided a reliable method of reconstruction for patients. Conclusion: Patients who were treated with NPWT had a longer LOS compared to other methods.